Diversity of disorders causing neonatal cholestasis - the experience of a tertiary paediatric centre in Germany - André eHoerning; André eHoerning; Simon eRaub; Alexander eDechene; Michelle eBrosch; Simone eKathemann; Peter eHoyer; Patrick eGerner; Patrick eGerner (Frontiers Media S.A., 2014)
Background and Objective: Rapidly establishing the cause of neonatal cholestasis is an urgent matter. The aim of this study was to report on the prevalence and mortality of the diverse disorders causing neonatal cholestasis in an academic center in Germany.Methods: Clinical chemistry and cause of disease were retrospectively analyzed in 82 infants (male n=42, 51%) that had presented with neonatal cholestasis to a tertiary medical center from January 2009 to April 2013. Results: Altogether, 19 disorders causing neonatal cholestasis were identified. Biliary atresia was the most common diagnosis (41%), followed by idiopathic cases (13%), progressive familial intrahepatic cholestasis (PFIC, 10%) and cholestasis secondary to total parenteral nutrition in preterm infants that was mediated by total parenteral nutrition (10%), α1AT deficiency, Alagille syndrome, portocaval shunts, mitochondriopathy, biliary sludge (all 2%) and others. Infants with biliary atresia were diagnosed with a mean age of 62 days, they underwent Kasai portoenterostomy ∼66 days after birth. The majority of these children (∼70%) received surgery within 10 weeks of age and 27% before 60 days. The two-year survival with their native liver after Kasai procedure was 12%. The time span between Kasai surgery and liver transplantation was 176 ± 73 days. Six children (7%), of whom 3 patients had syndromic and 1 nonsyndromic biliary atresia, died prior to liver transplantation. The pre- and posttransplant mortality rate for children with biliary atresia was ∼12% and ∼17%, respectively. Conclusion: Neonatal cholestasis is a severe threat associated with a high risk of complications in infancy and it thefore requires urgent investigation in order to initiate life saving therapy. Although in the last twenty years new causes such as the PFICs have been identifyed and newer diagnostic tools have been introduced into the clinical routine biliary atresia still represents the major cause.